SONGS AND POEMS OF THE "BIG CITY": TO THE QUESTION OF CULTURE AND LIFE OF MARIUPOL IN THE FIRST HALF OF THE 19th CENTURY (City: History, Culture, Society, 2020)
Тhere are several fragments of Іtalian, Russian and Ukrainian folk songs and poems among various texts, written with Greek letters, in the Urum manuscript dating from the first half of the 19th cent. The very presence of such texts, the character of their transcription indicates the spread of ІItalian, Russian and Ukrainian song culture and, in some degree, literature among the Turkish speaking Greeks of Mariupol in the first decades of their residence in Azov region.
Keywords: Urums; folk songs and poems; the Greeks of Azov region; Mariupol